Antibiotic resistance and the supragenome hypothesis - Charalambous, Bambos (Henry Stewart Talks, 2009)
Bacterial biofilms, genetic competence and exogenous DNA, Quorum sensing, The distributed-genome hypothesis and the finite supragenome model, Streptococcus pneumoniae and antibiotic resistance, Horizontal gene transfer and mosaic genes